The construct validity of the revised job diagnostic survey - M. A. Buys; C. Olckers; P. Schaap (South African Journal of Business Management, 2007)
The Job Characteristics Model, the accompanying Job Diagnostic Survey (JDS) and the proposed steps for improving motivation, satisfaction and performance have been functionally utilized in South Africa as a revised job redesign practice to address some critical human resources problems currently facing managers and human resources practitioners. The aim of the study was ] to determine the construct validity of the Revised Job Diagnostic Survey (JDS) in the South African context. The Revised JDS was evaluated using item analysis and confirmatory factor analysis. The finding of this study is in favour of the Revised JDS as a reliable and factorially valid instrument for South African use. The promising results of this study should pave the way for further research and the search for more conclusive evidence on the construct validity of the Revised JDS in the South African context.
Keywords: 650